Effects of Transcranial Direct Current Stimulation along with Drug Control on Working Memory, Automatized Rapid Naming and Aphasia Quotient in Patients with Stroke - Seyed Mojtaba Sohrevardi (Journal of Global Pharma Technology, 2017)
Aphasia after stroke in the left hemisphere is acommonsymptom. This people are often incomplete recovery intensive speech therapy experience. Direct electrical stimulation of the brain, which is a technique to stimulate the brain in neurological and psychiatric patients used. The aim of this study was to investigate the effects of stimulation on recovery of naming ability, working memory, and the non-fluent aphasia patients with aphasia and its effects were lasting. In this interventional study was conducted in 20 patients (12men and 6women, meanage 55/ 93years) with non-fluent aphasia after stroke were selected. Ratings of Aphasia quotient, working memory and naming ability to call them four times before and after treatment, after shamand twomonths after treatmentwas compared. 10 sessions of sham electrical stimulation (20min) and anodic and cathodic stimulation of10 sessions per patient (2mA- 20minutes) in the dorsal lateral perifrontal cortex received. Data analyzed was performed using cross over material with repeated measurements and friedman nonparametric test. The data showed that the ability of naming, working memory and aphasia quotient. In non-fluentaphasia aphasia patients after treatment and Two months after treatment compared with sham has grown significantly (p <.05).The results of this study seem to transcranial direct current stimulation can Sustained improvementin naming function, working memory and language abilities in patients with non-fluent aphasia is and can be used in the rehabilitation of these patients.